(untitled) (Veterinary Science, 2017)
Authors inform the results and conclusions of the experimental repair of lateral hernias with a muscular flap obtained from latissimus dorsi muscle in 15 dogs, males and females sexually mature. A 3x5 cm diaphragmatic defect was made after a thoracotomy in the 11º intercostal space and repaired with a muscle flap from latissimus dorsi muscle. After 60 days all animals were killed to observe macro and microscopic characteristics. In 95% of the cases the defects were repaired. In 11 canines adherences between lungs and the flap were seen. Fibrovascular tissue proliferation was observed histologically. We conclude that muscles flaps from Latissimus dorsi can be used to repair lateral defects